Penerapam Aplikasi Buku Tamu (SIKUTAMU) Pada Kantor Desa Parit Baru Kabupaten Kubu Raya Guna Mendukung Smart Village - Nurfia Oktaviani Syamsiah; Jubaidah; Eva Meilinda2; Dedi Saputra (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
SIKUTAMU is an application to assist guest data processing at the Parit Baru Village Office, Kubu Raya Regency, West Kalimantan. SIKUTAMU was granted by the BSI University Lecturer Team with a continuous procedure through the initial exposure stage, installation tutorials, application operations to evaluation of usage. The application of SIKUTAMU is expected to be one of the Smart Village support programs. This is because Parit Baru Village is one of the supporting villages for the provincial capital area with a very adequate internet network, as well as computer equipment is already available. However, guest data processing activities are still conventional. Once implemented, SIKUTAMU provides efficiency and effectiveness regarding the storage, processing, retrieval and reporting of guest data. So that SIKUTAMU can improve Village information services, towards Smart Village.